Endoscopic ultrasound-guided hepaticogastrostomy by puncturing both B2 and B3: a single center experience - Moaz Elshair; Kazuo Hara; Nozomi Okuno; Shin Haba; Takamichi Kuwahara; Asmaa Bakr; Abdou Elshafei; Mohamed Z. Abu-Amer (Korean Society of Gastrointestinal Endoscopy, 2024)
Endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) through ducts B2 or B3 is effective in most patients with biliary obstruction, because B2 and B3 commonly join together. However, in some patients, B2 and B3 do not join each other due to invasive hilar tumors; therefore, single-route drainage is insufficient. Here, we investigated the feasibility and efficacy of EUS-HGS through both B2 and B3 simultaneously in seven patients. We decided to perform EUS-HGS through both B2 and B3 to achieve adequate biliary drainage because these two ducts were separate from each other. Here, we report a 100% technical and overall clinical success rate. Early adverse effects were closely monitored. Minimal bleeding was reported in one patient (1/7) and mild peritonitis in one patient (1/7). None of the patients experienced stent dysfunction, fever, or bile leakage after the procedure. EUS-HGS through both B2 and B3 simultaneously is safe, feasible, and effective for biliary drainage in patients with separated ducts.